Antibody Therapies Targeting Complex Membrane Proteins. (November 2021) - To'a Salazar, Georgina; Huang, Ziyi; Zhang, Ningyan; Zhang, Xue-Guang; An, Zhiqiang
Abstract: In analyses of protein families that may serve as drug targets, membrane-associated G-protein-coupled receptors (GPCRs) dominate, followed by ion channels, transporters, and—to a lesser extent—membrane-bound enzymes. However, various challenges put such membrane proteins among key groups of underutilized opportunities for the application of therapeutic antibodies. Antibodies hold the promise of exquisite specificity, as they are able to target even specific conformations of a particular membrane protein, as well as adaptability through engineering into various antibody formats. However, the ease of raising and isolating specific, effective antibodies targeting membrane proteins depends on many factors. In particular, the generation of specific antibodies is easier when targeting larger, simpler, extracellular domains with greater uniqueness of amino acid sequence. The rareness of such ideal conditions is illustrated by the limited number of approved biologics for targeting GPCRs and other complex membrane proteins. Challenges in developing antibodies to complex membrane proteins such as GPCRs, ion channels, transporters, and membrane-bound enzymes can be addressed by the design of the antigen, antibody-generation strategies, lead optimization technologies, and antibody modalities. A better understanding of the membrane proteins being targeted would facilitate mechanism-based drug discovery. This review describes the advantages and challenges of targeting complex membrane proteins with antibodies and discusses the preparation of membrane protein antigens and antibody generation, illustrated by select examples of success.